PROSPEK DAN PROBLEMATIKA PELAKSANAAN APE - Irewati, Awani (Jurnal Penelitian Politik, 2025)
This essay attempts to analyseproblems andprospects ofthe APEC existence in dealing with the organizations principles implementation Afew years ago the Asia Pack Economic Cooperation APEC one ofthe most mea ningful organization in the region has been criticizedfor conducting insufficient efforts in addressing the 1997Asia crisis Nowadays the organization is currentlyfacing the internal detrimental challenges ofthe raising FTA based economic cooperations i e ASEAN China FTA ASEAN Japan FTA even bilateral based FTAs within the Asia Pacific region These FTAs could turn APEC out to be either breakable or even stronger It is hoped that thepowerful FTA basis should be a cornerstone towards the sturdy APEC The paper comes to the conclusion that the APEC which meets the two region Asia and Pacific is an convincinglyfeasible organization to remain taking the yearly dialogue between the developed and developing members This is truly becoming a lucrative opportunity for the members to express what they want to getfrom this organization